The chaetognatha community of the Agulhas Current: its structure and related properties - Stone, James Herbert (University of Cape Town, 2017)
A study has been made of a select group of marine zooplankton - the Chaetognatha. The analysis was done from a community viewpoint, that is, an objective technique was used to identify related groups of the Chaetognatha and these groups were then correlated with the distribution, abundance and fecundity of the individual species and with the existing hydrographical conditions. Competitive relationships among the species for habitats and niches were also examined.